THE ESSENTIALITY OF THE ROLE OF MEDIA IN LEARNING INFORMATION PROCESSING - Setuju; Dwiningrum; Rukiyati; Widowati (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
Media aims to stimulate students to remember what they have learned and helped obtain new information and stimulate student activity in providing feedback and feedback in the learning process. The media design in learning that is developed must be tailored to the needs of students and the expected learning outcomes. Information in the learning process is knowledge obtained from learning, experience, or instruction. Information Processing Theory deals with how people perceive their environment, how they enter information into memory, and how to recall information that has been obtained. Information processing theory is a cognitive approach to understanding how the human mind changes sensory information. The thought process is a mental activity of a person in the activity of being able to mix, match, combine, exchange, and sequence the concepts of perceptions and experiences obtained in a previous event. The process of obtaining information or knowledge in the memory process is greatly influenced by the perceptions of a person. Perception is a process of using the knowledge that is already owned (which is stored in memory) to detect or obtain and interpret stimuli (stimuli) received by sensory organs such as the eyes, ears, and nose. Information processes through three memories, namely sensory memory, short-term memory, and longterm memory, each of which has a storage capacity and causes the loss of information it has received. Learning media is one of the stimulants designed to help send messages to students and provide the same stimulation, equalize experiences, and cause the same perception of students. A set of external events designed to support some learning process that is internal in nature.